Regulasi Perbankan Sebagai Intermediary Dalam Pemberdayaan UMKM - Nurhotia Harahap (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2019)
The banking intermediary function is the pulse for the economy, bearing in mind that business actors as economic drivers need banking funds for their business activities, including the real sector, especially MSMEs. This is in line with the objectives of the Indonesian Banking to support the implementation of national development in order to improve equity, economic growth, and national stability towards improving the welfare of the people at large. Looking at the supporting factors above, it can be seen the relationship between the real sector and banks. At present, the Bank is not considered to support the financing of the real sector due to the complexity of the Bank's administrative procedures. The problem of developing the real sector through empowering MSMEs rests among other things on capital problems, namely the difficulty of gaining banking access through lending. MSMEs also have a strategic position, role and potential in realizing job creation. Income participation, economic growth and poverty reduction. Solid MSMEs can be the main pillars for the realization of broad community welfare. Therefore, to realize its function and develop its potential, MSMEs need to be supported by financing, especially in the real sector.